Razvoj poklicev na področju trajnostnega urbanizma - Uršič, Matjaž (Teorija in praksa, 2017)
The article addresses occupational development in the field of sustainable urbanism. To this end, examples of sustainable neighbourhoods are analysed: Hammarby Sjöstad (Stockholm), Vauban (Freiburg), and GWL-Terrein (Amsterdam). The introduction presents the issues of understanding the operation of occupational groups, their competencies, and occupational professionalisation, followed by an empirical analysis of existing sustainable neighbourhoods. Based on the analysis and interpretation of its findings, the article then provides concrete recommendations for occupational and human resource development in the field of sustainable urbanism in Slovenia and Europe. These derive from the premise that sustainable urbanism, which tries to solve spatial as well as social, cultural and economic problems, requires that social, natural science and technical occupations be adequately represented.
Keywords: City planning; Neighbourhood; Occupations; Poklici; Soseska; Sustainable development; Trajnostni razvoj; Urbanizem